Amorphous silicon dioxide powder and resin composition containing the same

By adjusting the particle size distribution and specific surface area of ​​amorphous silica powder, the problem of insufficient fluidity of liquid sealing materials in the prior art is solved, and the development of high-flow resin composition is realized, and the demand for miniaturization and thinning of electronic equipment is met.

CN115989283BInactive Publication Date: 2025-02-28DENKA CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202180052343.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2020-08-25
Filing Date
2021-08-17
Publication Date
2025-02-28
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The prior art is difficult to provide liquid sealing materials with high flowability, and cannot meet the needs of miniaturization and thinning of electronic equipment.

Method used

By adjusting the particle size distribution and specific surface area of ​​the amorphous silica powder, it is ensured that the most frequency particle diameter in the particle size frequency distribution is within the range of 1 to 10 μm, the particle frequency of the particle size less than 0.50 μm is more than 1.0%, and the specific surface area is within the range of 1 to 12 m2/g.

Benefits of technology

It has achieved excellent fluidity of the resin composition and is suitable as a liquid sealing material to meet the needs of miniaturization and thinning of electronic equipment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004092931370000091
    Figure BDA0004092931370000091
Patent Text Reader

Abstract

The present invention provides an amorphous silicon dioxide powder and a resin composition filled with the amorphous silicon dioxide powder, by which a liquid sealing material having excellent filling properties and storage properties can be obtained. More specifically, in the present invention, the frequency of particles with a particle size smaller than 0.50 μm in the particle size frequency distribution is 1.0% or more, and the particle size frequency distribution is 1 to 12 μm. 2 Amorphous silicon dioxide powder was prepared in a manner with a specific surface area of ​​1.547 W / g.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to an amorphous silicon dioxide powder and a resin composition, and more particularly to an amorphous silicon dioxide powder which is suitable as a filler for a liquid sealing material and a resin composition containing the amorphous silicon dioxide powder. Background Art

[0002] In recent years, the miniaturization, lightness, and high performance of electronic devices can be achieved through the high integration of semiconductor components, the multi-pin and lightness of semiconductor packages, and the high-density mounting technology on circuit boards. Recently, surface mount packages such as quad flat packages (QFP) that can be mounted at high density have become the mainstream, replacing the existing plug-in packages, and the demand for further miniaturization and lightness is also increasing.

[0003] Among such package mounting technologies, bare chip mounting technology, which directly mounts semiconductor components on circuit boards, has attracted much attention as a mounting technology for semiconductors and electronic devices that require small size, thinness, light weight, high-density mounting, short construction period, and low cost. As a method of electrical connection between a bare chip mounted chip and a substrate, there are wire bonding, flip chip bonding, and the like. Most of the mounted chips are sealed with liquid sealing materials in accordance with the need for chip protection, filling reinforcement, and the like.

[0004] Prior art literature

[0005] Patent Literature

[0006] Patent Document 1: Japanese Patent No. 4244259

[0007] Patent Document 2: Japanese Patent No. 5265097 Summary of the invention

[0008] As described above, electronic devices are becoming smaller, thinner and lighter, and resin compositions used for sealants are also required to have high fluidity.

[0009] The present invention has been made in view of the above circumstances, and an object of the present invention is to provide an amorphous silica powder and a resin composition filled with the amorphous silica powder, which are suitable for obtaining a liquid sealing material having excellent fluidity.

[0010] The present inventors have successfully solved the above-mentioned problems by appropriately adjusting the particle size distribution and specific surface area of ​​the amorphous silica powder.

[0011] That is, one aspect of the present invention is to provide an amorphous silicon dioxide powder, characterized in that in the particle size frequency distribution, the frequency of particles with a particle size of less than 0.50 μm is 1.0% or more, and the particle size of 1 to 12 μm is 10 μm or more. 2 / g specific surface area.

[0012] The specific surface area of ​​the amorphous silicon dioxide powder of the present invention is 3 to 10.5 m 2 / g.

[0013] The amorphous silica powder of the present invention has an oversize cumulative distribution of particles having a particle size of 13 μm or more of 1% by mass or less.

[0014] Furthermore, the amorphous silica powder of the present invention has a melting rate of 95% or more, and a total concentration of uranium and thorium elements of 10 ppb or less.

[0015] Another aspect of the present invention provides a resin composition characterized by containing 10 to 90% by mass of the amorphous silica powder of the present invention.

[0016] The resin composition of the present invention is a liquid sealant.

[0017] The resin composition containing the amorphous silica powder of the present invention has excellent viscosity characteristics and is therefore particularly useful as a liquid sealing material. DETAILED DESCRIPTION

[0018] Hereinafter, the present invention will be described in further detail.

[0019] <Amorphous silica powder>

[0020] In the present invention, the amorphous silica powder having a most frequent particle size in the range of 1 to 10 μm in the particle size frequency distribution is made to contain a predetermined amount or more of particles having a particle size of less than 0.50 μm, and the specific surface area is adjusted to a predetermined range. This adjustment can improve the fluidity of the resin composition.

[0021] In the particle size frequency distribution of the amorphous silica powder of the present invention, the most frequent particle size is in the range of 1 to 10 μm. If the most frequent particle size in the particle size frequency distribution of the amorphous silica powder exceeds 10 μm, the above-mentioned problem occurs. On the other hand, when the particle diameter of the powder is small and the most frequent particle size in the particle size frequency distribution is less than 1 μm, the viscosity of the liquid sealing material becomes too high and the filling amount of the powder cannot be increased. The lower limit value may be above 1.5 μm, may be above 2.0 μm, may be above 2.5 μm, may be above 3.0 μm, or may be above 3.2 μm. The upper limit value may be below 8.0 μm, may be below 7.0 μm, may be below 6.0 μm, may be below 5.0 μm, or may be below 4.2 μm. The most frequent particle size here refers to the particle size showing the highest frequency in the particle size distribution of the powder obtained by the measurement method described later. In addition, when the mode particle size of the amorphous silicon dioxide powder as a raw material exceeded 10 μm, classification was performed to adjust the particle size distribution.

[0022] In addition, in the peak with a maximum value in the range of 1 to 10 μm, if the frequency of particles with a particle size of 0.50 to 1.83 μm is set to less than 2.0%, the fluidity of the amorphous silica powder can be further improved. More preferably, it is less than 1.5%, less than 1.0%, less than 0.5%, and can be 0.0%. The method of setting the frequency of particles with a particle size of 0.50 to 1.83 μm to less than 2.0% can adopt a method known in the past, and an example can be a method of dividing the coarse powder side and the fine powder side using a precision wind classifier. It should be noted that the frequency of particles with a particle size of 0.50 to 1.83 μm is a value obtained using the particle size distribution measurement method described later.

[0023] The number of peaks showing a maximum frequency in the range of 1 to 10 μm in the particle size frequency distribution may be one or more peaks from the viewpoint of obtaining the effects of the present invention.

[0024] The frequency of the frequency maximum of the first peak showing the frequency maximum in the range of 1 to 10 μm in the particle size frequency distribution may be 5% by volume or more. The lower limit of the frequency may be 9% by volume or more. The upper limit of the frequency may be 20% by volume or less, 15% by volume or less, or 14% by volume or less.

[0025] In addition, the frequency of particles with a particle size of less than 0.50 μm in the amorphous silica powder of the present invention is more than 1.0%. Particles with a particle size of less than 0.50 μm are added to particles with a most frequent particle size of 1 to 10 μm, so that the fluidity of the amorphous silica powder can be improved. The upper limit of the frequency of particles with a particle size of less than 0.50 μm can be less than 10%, less than 9%, less than 7%, less than 5%, less than 4%, or less than 3%. It should be noted that the frequency of particles with a particle size of less than 0.50 μm is a value obtained by the particle size distribution measurement described later.

[0026] The frequency of particles with a particle size of less than 0.50 μm is preferably at least in the range of 0.10 μm to 0.50 μm from the viewpoint of improving the effect of the present invention. In addition, the frequency may not be entirely in the range of 0.10 μm to 0.50 μm, but the frequency is preferably in the range of 0.1 to 0.3 μm.

[0027] In addition, in the frequency distribution of particle size, particles with a particle size of less than 0.50 μm may be included in a peak different from the peak having a local maximum in the range of 1 to 10 μm. For example, there are cases where there is a peak having a local maximum in the range of 1 to 10 μm and a peak having a local maximum in a range of less than 0.50 μm, and a case where there is a peak having a local maximum in the range of 1 to 10 μm and a peak having a local maximum in a range of less than 0.50 to 1 μm and a peak having a local maximum in a range of 0.50 to less than 1 μm having a frequency of less than 0.50 μm and 1.0% or more. It should be noted that in either case, the tails of the above two peaks may or may not overlap.

[0028] In addition, particles with a particle size smaller than 0.50 μm may be part of a peak having a local maximum in the range of 1 to 10 μm, for example, when a peak having a local maximum in the range of 1 to 10 μm has a frequency of less than 0.50 μm and 1.0% or more.

[0029] In addition, a part of the particles with a particle size of less than 0.50 μm may be included in a peak having a local maximum in the range of 1 to 10 μm, and another part may be included in a peak different from the peak having a local maximum in the range of 1 to 10 μm. For example, there is a case where the tail of the peak having a local maximum in the range of 1 to 10 μm has a frequency of less than 0.50 μm and a peak having a local maximum in less than 0.50 μm.

[0030] In the present invention, it is preferred that the peak having a local value at less than 0.50 μm and the peak having a local value in the range of 1 to 10 μm are independent of each other. However, even in this case, the tails of the respective peaks may or may not overlap.

[0031] In addition, in the frequency distribution of particle size, when particles with a particle size smaller than 0.50 μm are included in a peak different from the peak having a maximum value in the range of 1 to 10 μm, there is no particular limitation on the number of peaks having a frequency smaller than 0.50 μm, and the number of peaks may be one or more.

[0032] In addition, when particles with a particle size of less than 0.50 μm are included in a peak different from the peak having a maximum value in the range of 1 to 10 μm, the peak including particles with a particle size of less than 0.50 μm may have a frequency of more than 0.50 μm or may not have a frequency. When having a frequency of more than 0.50 μm, preferably 80% or more of the frequency is the frequency of less than 0.50 μm.

[0033] In addition, when the peak containing particles with a particle size smaller than 0.50 μm is a peak different from the peak having a local maximum in the range of 1 to 10 μm, the local maximum of the peak containing particles with a particle size smaller than 0.50 μm is preferably in the range of more than 0.1 μm and less than 0.4 μm.

[0034] In addition, in the amorphous silicon dioxide powder of the present invention, the specific surface area is set to 1 to 12 m 2 / g. If the specific surface area of ​​amorphous silicon dioxide powder exceeds 12m 2 / g, the tendency of agglomeration between the microparticles increases, and the fluidity of the amorphous silica powder decreases. The upper limit can be 10.5m 2 / g or less, can be 9m 2 / g or less, can also be 8m 2 / g or less. On the other hand, when the specific surface area is less than 1m 2 When the amorphous silica powder has a density of 0.1447 W / g, the fluidity is reduced because the amorphous silica powder is not easy to form a close-packed structure. The lower limit is preferably 3 m 2 / g or more, more preferably 4m 2 / g or more, more preferably 5m 2 / g or above.

[0035] In particular, in order to improve the effect of the present invention, when the peak containing particles with a particle size of less than 0.50 μm is different from the peak having a maximum value in the range of 1 to 10 μm, the specific surface area of ​​the amorphous silica powder tends to decrease, but the specific surface area can be adjusted to the desired range by increasing the amount of particles with a particle size of less than 0.50 μm used.

[0036] In particular, in order to improve the effect of the present invention, in the peak having a maximum value in the range of 1 to 10 μm, when the frequency of particles with a particle size of 0.50 to 1.83 μm is set to less than 2.0%, the specific surface area of ​​the amorphous silica powder tends to decrease, but the specific surface area can be adjusted to the desired range by increasing the use amount of particles with a particle size of less than 0.50 μm.

[0037] In the amorphous silica powder of the present invention, d10, d50, and d90 are not particularly limited. d10 can be 0.5 to 4.0 μm. d50 can be 3.5 to 7.0 μm. d90 can be 4.0 to 9.0 μm. Among them, from the viewpoint of obtaining the effect of the present invention, d10 is preferably 1.5 to 3.5 μm. d50 is preferably 3.0 to 5.0 μm. d90 is preferably 4.0 to 7.0 μm. Here, d10, d50, and d90 are particle sizes with cumulative values ​​of 10%, 50%, and 90% in the cumulative distribution of particle sizes, respectively. For amorphous silica powder, the particle size distribution is obtained by the method described later, shown as a volume distribution, and the refractive index is set to 1.5.

[0038] The amorphous silica powder of the present invention preferably has a sieve oversize cumulative distribution of particles with a particle size of 13 μm or more of less than 1% by mass. It can be 0% by mass. By reducing the number of coarse particles, it can be preferably used even when the height between the mounting substrate and the chip is a narrow gap. In addition, by reducing the number of coarse particles, the amorphous silica powder can further easily form a densest packing structure, and the fluidity of the liquid sealing material is improved.

[0039] The amorphous silica powder of the present invention may contain other components (additives, etc.) other than the amorphous silica powder within the range that does not impair the effect of the present invention. For example, the other components may be 5% by mass or less, 3% by mass or less, 1% by mass or less, or 0% by mass.

[0040] In addition, the amorphous silicon dioxide powder of the present invention may not contain uranium and thorium as other components depending on the application. In the case of a liquid sealing material for sealing a semiconductor, from the viewpoint of suppressing the defective generation rate of memory rewriting, the total concentration (content) of uranium and thorium is preferably less than 10 ppb.

[0041] From the viewpoint of making the thermal expansion coefficients of the semiconductor wafer and the liquid sealing material close to each other, the amorphous silica powder of the present invention is preferably produced by melting crystalline silica at high temperature or by a synthesis method. Therefore, the melting rate of the amorphous silica powder of the present invention is preferably 95% or more.

[0042] The shape of the amorphous silica powder may be any of spherical, crushed, needle-shaped, frame-shaped, etc. Spherical amorphous silica powder is most suitable from the viewpoint of filling as much as possible and reducing the thermal expansion coefficient of the liquid sealing material.

[0043] The amorphous silica powder of the present invention may be mixed with other inorganic fillers for use. The other inorganic fillers may be different types of materials such as alumina powder and magnesia powder, or may be the same amorphous silica powder but with different particle size distributions.

[0044] The particle size frequency distribution of the amorphous silica powder of the present invention is measured using a Coulter particle size distribution analyzer LS13 320 (Coulter Beckman Co.) As for the measurement conditions, a silica aqueous solution dispersed in advance by an ultrasonic homogenizer is put into the device and analyzed under the condition of a refractive index of 1.5.

[0045] In order to produce the amorphous silicon dioxide powder of the present invention, it can be carried out by mixing or classifying the appropriate amount of powders having different particle sizes. From an industrial point of view, classification based on a classifier is preferred, and the classification operation can be any of a dry method and a wet method. It should be noted that from the perspective of productivity and removal of coarse particles, a dry precision wind classifier is preferably used.

[0046] <Resin composition>

[0047] Next, the resin composition of the present invention will be described.

[0048] When the amorphous silica powder of the present invention is mixed with a resin, the amorphous silica powder of the present invention can be used alone, or conventional spherical and crushed powders can be used simultaneously. The mixing ratio of the resin cannot be determined uniformly according to the required properties of the resin composition, and the mixing ratio of the amorphous silica powder of the present invention is selected in the range of 10 to 90 mass %.

[0049] In the present invention, for the material other than the amorphous silicon dioxide powder coordinated to the liquid sealing material, additive, it is not particularly limited, within the scope of not damaging the effect of the present invention, it is also possible to use the powder commonly used in the past.Other components (resin and components other than the amorphous silicon dioxide powder) can be less than 10 mass %, less than 5 mass %, less than 3 mass %, less than 1 mass %.In addition, the purpose of amorphous silicon dioxide powder is also not limited to sealing material, and it is also possible to use the filler purposes or anti-adhesion materials of adhesive, coating, adhesive tape, resin substrate, etc.

[0050] As a material or additive other than the amorphous silicon dioxide powder matched to the liquid sealing material, an epoxy resin that is liquid at room temperature can be cited as a typical example. If the epoxy resin that can be used has more than two epoxy groups in one molecule, it is not particularly limited. Specifically, bisphenol A type epoxy resin, bisphenol F type epoxy resin, alicyclic epoxy resin, novolac type epoxy resin, cresol novolac type epoxy resin, naphthalene diol type epoxy resin, etc. can be cited. These epoxy resins can be used alone or in combination. In this case, in order to improve the adhesion of the liquid epoxy resin and the amorphous silicon dioxide powder of the present invention, the amorphous silicon dioxide powder of the present invention is surface treated by utilizing a silane-based surface treatment agent, or added immediately after the surface treatment is implemented, so that further excellent properties can be obtained.

[0051] The resin composition of the present invention may further contain, as required, a curing agent such as methyltetrahydrophthalic anhydride, methylimidic anhydride, or the like, a curing accelerator such as dicyandiamide, a high melting point imidazole compound, a silane coupling agent such as γ-glycidoxypropyltrimethoxysilane, γ-aminopropyltriethoxysilane, or the like, a pigment such as carbon black, a flame retardant such as a halogen compound, a phosphorus compound, or the like, a flame retardant such as antimony trioxide, or a low stress imparting agent such as rubber or an organic silicon compound.

[0052] Example

[0053] <Preparation of amorphous silicon dioxide powder>

[0054] The amorphous silica powder of the preparation example of the present invention was prepared according to the following steps. It should be noted that commercially available amorphous silica was used as a raw material. It should be noted that the raw material had a single peak with a mode particle size in the range of 1 to 10 μm.

[0055] [Coarse powder classification]

[0056] First, the raw material amorphous silica powder was coarsely classified to remove large particles. The cumulative distribution of the oversize of particles having a particle size of 13 μm or more is shown in Table 1. It should be noted that in the examples, the cumulative distribution of the oversize of particles having a particle size of 13 μm or more was 0.0 mass %.

[0057] [Micro powder classification]

[0058] Next, for some examples, the frequency of particles with a particle size of 0.50 to 1.83 μm was adjusted in the method of dividing the fine powder side using a precision wind classifier. The frequency of particles with a particle size of 0.50 to 1.83 μm is shown in Table 1. It should be noted that in the examples, the frequency in the most frequent particle size range of 1 to 10 μm was 9.3 to 13.6% by volume.

[0059] [Ultrafine powder compounding]

[0060] Next, for the examples, amorphous silica powder (ultrafine powder with a particle size (median diameter) of 0.10 μm or 0.14 μm) with a smaller particle size than the amorphous silica powder obtained in the process up to the fine powder classification is blended at the internal addition ratio shown in Table 1. In this blending, all examples select a particle size with a frequency of occurrence in the range of 0.1 to 0.3 μm. In addition, the blending is performed in a manner that a peak different from the peak with a maximum value in the range of 1 to 10 μm appears. In addition, in the example with a particle size of 0.14 μm, the maximum value of the peak containing particles with a particle size of less than 0.50 μm is in the range of 0.1 to 0.3 μm.

[0061] <Preparation of resin composition>

[0062] A liquid epoxy resin (JER-807 (manufactured by Mitsubishi Chemical Corporation)) and the silica of the examples or comparative examples were mixed at a ratio of 35:65 (wt%).

[0063] <Evaluation of amorphous silica powder and resin composition>

[0064] The property values ​​of the obtained amorphous silica powder and the resin composition were measured as follows. The measurement methods are as follows.

[0065] [Evaluation of amorphous silica particles]

[0066] (1) Specific surface area

[0067] The BET theory is applied to the adsorption isotherm measured by the gas adsorption method to determine the specific surface area (BET value) (BET method).

[0068] (2) Particle size

[0069] The particle size frequency distribution and the particle size cumulative distribution were measured using the Coulter method which has no influence on the sample density.

[0070] The median diameter d (μm) of the ultrafine powder is the BET value measured using the BET method, based on the relative density of silica particles (density 2.2 g / cm 3 ) is calculated using the following formula.

[0071] [Mathematical formula 1]

[0072] Median diameter d = 6 / ((BET value) × 2.2)

[0073] (3) Melting rate

[0074] The melting rate of the present invention can be measured by using a powder X-ray diffraction device to perform X-ray diffraction analysis of the sample in the range of 26° to 27.5° of 2θ of CuKα rays, based on the intensity ratio of specific diffraction peaks. That is, crystalline silica has a main peak at 26.7°, while molten silica does not exist at this position. If molten silica and crystalline silica are mixed, a peak height of 26.7° corresponding to these ratios can be obtained. Therefore, based on the ratio of the X-ray intensity of the sample to the X-ray intensity of the crystalline silica standard sample, the crystalline silica mixing rate (X-ray intensity of the sample / X-ray intensity of the crystalline silica) is calculated, and the melting rate can be calculated using the following formula.

[0075] [Mathematical formula 2]

[0076] Melting rate (%) = (1-crystalline silica mixing rate) × 100

[0077] (4) Uranium and thorium content

[0078] The contents of uranium and thorium were determined using an inductively coupled plasma mass spectrometer (ICP-MS).

[0079] [Evaluation of resin composition]

[0080] The viscosity of the resin composition after mixing was measured by liquid chromatography (shear rate: 1 (1 / s), temperature: 30° C.).

[0081] [Evaluation results]

[0082] Table 1 shows the physical property values ​​of the preparation conditions (powder classification conditions, blending) of each amorphous silica powder, powder properties, and flow properties (viscosity) of a resin composition using each amorphous silica powder.

[0083] Table 1

[0084]

[0085] Industrial Applicability

[0086] The present invention is filled with particles having a particle size frequency distribution in which the most frequent particle size is in the range of 1 to 10 μm, the frequency of particles having a particle size of less than 0.50 μm is 1.0% or more, and having a particle size frequency distribution of 1 to 12 μm. 2 The resin composition containing amorphous silica powder having a specific surface area of ​​1000 μg / g is excellent in fluidity and is therefore suitable for a sealing agent for semiconductor devices.

Claims

1. An amorphous silicon dioxide powder, characterized in that: In the particle size frequency distribution, the most frequent particle size is in the range of 3.0 to 4.2 μm, the frequency of particles with a particle size less than 0.50 μm is 1.0% to 9%, and the frequency of particles with a particle size of 3 to 10.5 μm is 1.0% to 9%. 2 / g of specific surface area, and the cumulative distribution of oversize particles with a particle size of 13μm or more is less than 1 mass %, and in the peak with a maximum value in the range of 1 to 10μm, the frequency of particles with a particle size of 0.50 to 1.83μm is less than 2.0%.

2. The amorphous silicon dioxide powder according to claim 1, wherein The melting rate is 95% or more.

3. The amorphous silicon dioxide powder according to claim 1 or 2, wherein The total content of uranium and thorium is 10 ppb or less.

4. A resin composition, characterized in that The amorphous silicon dioxide powder according to any one of claims 1 to 3 is contained in an amount of 10 to 90% by mass. The resin composition according to claim 4 , which is a liquid sealing material.

Citation Information

Patent Citations

  • Metal oxide powder and resin composition

    JP2001199713A

  • Amorphous silica powder, resin composition, and semiconductor encapsulation material

    JP2019182715A

  • Composite material and method of manufacturing the same

    US20050154087A1